Encapsidation of viral DNA requires the adenovirus L1 52/55-kilodalton protein - Gustin, K E; Imperiale, M J (Journal of virology, 1998)
Previous work demonstrated that the adenovirus L1 52/55-kDa protein is required for assembly of viral particles, although its exact role in the assembly process is unclear. The 52/55-kDa protein's early expression, however, suggests that it might have other roles at earlier times during infection. To uncover any role the 52/55-kDa protein might have at early times and to better characterize its role in assembly, a mutant adenovirus incapable of expressing the 52/55-kDa protein was constructed (H5pm8001). Analysis of the onset and extent of DNA replication and late protein synthesis revealed that H5pm8001-infected 293 cells entered the late stage of infection at the same time as did adenovirus type 5 (Ad5)-infected cells. Interestingly, H5pm8001-infected cells displayed slightly lower levels of replicated viral DNA and late proteins, suggesting that although not required, the 52/55-kDa protein does augment these activities during infection. Analysis of transcripts produced from the major late and IVa2 promoters indicated a slight reduction in H5pm8001-infected compared to Ad5-infected cells at 18 h postinfection that was not apparent at later times. Analysis of particles formed in H5pm8001 cells revealed that empty capsids could form, suggesting that the 52/55-kDa protein does not function as a scaffolding protein. Subsequent characterization of these particles demonstrated that they lacked any associated viral DNA. These findings indicate that the 52/55 kDa-protein is required to mediate stable association between the viral DNA and empty capsid and suggest that it functions in the DNA encapsidation process.